Impacts of Saharan Mineral Dust on Air‐Sea Interaction over North Atlantic Ocean Using a Fully Coupled Regional Model. Issue 4 (17th February 2021) - Chen, Shu‐Hua; Huang, Chu‐Chun; Kuo, Yi‐Chun; Tseng, Yu‐Heng; Gu, Yu; Earl, Kenneth; Chen, Chih‐Ying; Choi, Yonghan; Liou, Kuo‐Nan
Abstract: This study examines the modifications of air‐sea coupling processes by dust‐radiation‐cloud interactions over the North Atlantic Ocean using a high‐resolution coupled atmosphere‐wave‐ocean‐dust (AWOD) regional model. The dust‐induced mechanisms that are responsible for changes of sea surface temperature (SST) and latent and sensible heat fluxes (LHF/SHF) are also examined. Two 3‐month numerical experiments are conducted, and they differ only in the activation and deactivation of dust‐radiation‐cloud interactions. Model results show that the dust significantly reduces surface downward radiation fluxes (SDRF) over the ocean with the maximum change of 20–30 W m −2 . Over the dust plume region, the dust effect creates a low‐pressure anomaly and a cyclonic circulation anomaly, which drives a positive wind stress curl anomaly, thereby reducing sea surface height and mixed layer depth. However, the SST change by dust, ranging from −0.5 to 0.5 K, has a great spatial variation which differs from the dust plume shape. Dust cools SST around the West African coast, except under the maximum dust plume ridge, and extends westward asymmetrically along the northern and southern edges of the dust plume. Dust unexpectedly warms SST over a large area of the western tropical North Atlantic and north of the dust plume. These SST changes are controlled by different mechanisms. Unlike the SST change pattern, the LHF and SHF changes are mostly reduced underneath the dust plume region, though they are different in detail due to different dominant factors, and increased south of the dust plume over the tropic. Plain Language Summary: This study investigates how the common Sahara dust can change the atmosphere and ocean dynamical processes using a high‐resolution model. Dust indeed affects the ocean sea surface temperature distribution as expected, but some surprising warm sea surface temperature features are found and their mechanisms are discussed. Key Points: Dust‐radiation‐cloud interactions mainly cool SST offshore the North Africa and warm SST over the southwestern dust plume region Dust reduces upward LHF and SHF underneath the dust plume region and increases the values south of the dust plume Changes of SST/LHF/SHF by dust are not only attributed to the dust‐induced SDRF reduction but also changes of WSC and upper‐ocean dynamic